PENGATURAN HUKUM CALON LEGISLATIF MANTAN NARAPIDANA - Salim Fauzi Lubis; Ismail Ismail; Mina Mardiana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
Election or local election is a way of channeling the rights of every principle community, which means that the right to vote and vote is contained in his constitutional rights as citizens. In article 28 letter D of the Republic of Indonesia Republic of 1945 which reads that